Uncertainty in modelling the detachment of soil by rainfall - Parsons, Anthony J.; Gadian, Alan M. (Earth surface processes and landforms, 2000)
In process‐based models of soil erosion, soil detachment by rainfall is commonly modelled as a simple function of rainfall intensity, based on the assumption of a relationship between drop‐size distribution and intensity. Here we show that rainfall kinetic energy (and hence soil detachment) does not bear a simple relationship to intensity. For low‐intensity rainfall, observed variations in drop‐size distributions indicate that soil detachment, at a given rainfall intensity, may vary by about a factor of two. Comparable estimates of variation in soil detachment at high rainfall intensity are not possible because of a dearth of observational data on variation in drop‐size distributions in high‐intensity rainfall. Variation in drop‐size distributions in natural rainfall may, therefore, account for a significant component of differences between observed soil detachment and that predicted by models of soil erosion. Copyright © 2000 John Wiley & Sons, Ltd.